Fuera, dentro, en y sobre el arte y el espacio virtual - Paulina Macías (Les Cahiers ALHIM)
This text stems from the impulse to wonder if the idea of ​​virtuality and its prevalence in museum practices after the pandemic is essentially new or emanates from explorations of the artistic practices of conceptual art, rather already established, for more than a year. century that play with the idea of ​​immateriality that today is the constant. To do so, in addition to taking a brief tour of possible definitions of virtual space, three approach perspectives are proposed with their respective examples: For, where we reflect on the museum exercises that are done for the internet, In and from, where they present works that are possible only in virtuality and Sobre, which talks about projects that, rather than using virtuality as a form, recover them in their ways of creating content.